Bandgap control of α-Fe2O3 nanozymes and their superior visible light promoted peroxidase-like catalytic activity. (19th September 2018) - Zhu, Mingyun; Dai, Yunqian; Wu, Yanan; Liu, Ken; Qi, Xiaomian; Sun, Yueming
Abstract: Iron oxide nanoparticles (NPs) possessing peroxidase-like catalytic activity have been widely explored in recent decades, owing to their high stability against harsh conditions, low cost, flexibility in structure design and composition, adjustable activities and excellent biocompatibility in comparison with natural enzymes. Recently, a lot of great achievements have been made in this field of iron oxide nanozymes, however, this research has now reached a bottleneck in that the maximum activity enhancement is difficult to achieve via a material design. Hence, in this work, visible light was introduced to improve the peroxidase-like activity of Fe2 O3 NPs synthesized via a combination of electrospinning technology and hydrothermal reaction. Our results showed that with the assistance of visible light, Fe2 O3 NPs exhibited at least 2.2-fold higher peroxidase activity than those tested under darkness, confirming the superiorly visible light promoted peroxidase-like catalytic activity of Fe2 O3 NPs. Furthermore, the affinity and maximum reaction velocity of Fe2 O3 nanoflowers (bandgap = 1.78 eV) towards 3, 3', 5, 5'-tetramethylbenanozymeidine (TMB) were at least over 3.7 and 4.3 times greater than in Fe2 O3 nanocubes (bandgap = 2.08 eV), suggesting that the reaction performance of semiconductors could be controlled by proper adjustment of the bandgap. Moreover, the Fe2 O3 NPs were also successfully utilized to detect glucose. Herein, we believe that the present work exhibits a fascinating perspective for peroxidase-like catalytic fields.